PENERAPAN METODE MATCHING MATH UNTUK MENINGKATKAN PRESTASI BELAJAR IPA MATERI KLASIFIKASI MAKHLUK HIDUP KELAS VIIA SMPN 2 KWADUNGAN NGAWI TAHUN PELAJARAN 2014/2015 - Trihastuti, Anik (Jurnal Florea, 2015)
Results of the classification of living beings learning reflection data showed 54 % of students pass the study and 45 % of students have not been thoroughly studied, so that the necessary process of learning improvement. The purpose of this study improve learning achievement IPA material classification of living things. The study design using classroom action research (PTK) through the application of math matching method. Research conducted at SMPN 2 Kwadungan Ngawi, research subjects students of class VII A numbered 24 students, Data collection techniques with methods of observation and tests. Data were analyzed descriptively. The results showed , the application of math matching methods improve learning achievement, the first cycle value completeness 63 %, 71 % second cycle and third cycle 92 %, the average value of the first cycle class 72.4, 72.4 second cycle, and the cycle III 78. Keywords : learning achievement, mastery learning, matching math